(untitled) (Sir Salimullah Medical College Journal, 2022)
An aneurysmal bone cyst (ABC) is a benign, expansile, non-neoplastic lesion of the bone, characterized by channels of blood and spaces that are separated by fibrous septae. Giant ABC is an uncommon condition and can be difficult to handle because of the destructive effect of the cyst on the bones and the compressive effect on the nearby structures, especially in weight-bearing bones of the body commonly affecting the younger age group. Here, we present a case of a bone lesion in the left proximal femur of a six-year-old child, who had a previous history of right-sided Nephrectomy due to Wilms’ tumor (WT). Follow-up computed tomography of the abdomen revealed a peritoneal metastatic deposit, abdominal lymphadenopathy & additional expansile osteolytic lesion at the proximal left femur and considered all as metastatic deposits. Magnetic resonance imaging of the left hip demonstrated an expansile multiloculated heterogeneously enhancing cystic lesion with a fluid-fluid level in the upper shaft of the left femur typical for ABC (Aneurysmal bone cyst). At the same time, the scintigraphy report shows it’s a neoplastic lesion. Finally, the biopsy report confirmed it’s a benign lesion which correlates with the MRI findings. Despite its rarity, metastatic Wilms’ tumor to bone should be considered in a child though in WT metastasizes to bones very late. So, benign-appearing bone lesions are sometimes misdiagnosed as metastatic lesions may arise difficulty in diagnosis, management & treatment plans due to the co-existence of other pathologies. Sir Salimullah Med Coll J 2022; 30: 190-192